2012
DOI: 10.1007/s10522-012-9406-3
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin: from top to bottom

Abstract: Serotonin is a monoamine neurotransmitter, which is phylogenetically conserved in a wide range of species from nematodes to humans. In mammals, age-related changes in serotonin systems are known risk factors of age-related diseases, such as diabetes, faecal incontinence and cardiovascular diseases. A decline in serotonin function with aging would be consistent with observations of age-related changes in behaviours, such as sleep, sexual behaviour and mood all of which are linked to serotonergic function. Despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 257 publications
2
93
1
4
Order By: Relevance
“…Brainderived serotonin increases osteoblast numbers and decreases bone resorption, therefore increasing bone mass. Conversely, gut-derived serotonin acts to inhibit bone formation and increased circulating serotonin has been associated with lower bone density [45]. Age-related changes in drug absorption, metabolism, and blood-brain barrier permeability may also influence levels of serotonin.…”
Section: Discussionmentioning
confidence: 99%
“…Brainderived serotonin increases osteoblast numbers and decreases bone resorption, therefore increasing bone mass. Conversely, gut-derived serotonin acts to inhibit bone formation and increased circulating serotonin has been associated with lower bone density [45]. Age-related changes in drug absorption, metabolism, and blood-brain barrier permeability may also influence levels of serotonin.…”
Section: Discussionmentioning
confidence: 99%
“…[37,38,40,41] 5-OH tryptamine performance as a tissue hormone, neurotransmitter and neuromodulator. [42,43] It is one of the most important neurotransmitters in the central nervous system (CNS) regulating multiple physiological functions such as body temperature, appetite, sleep, mood and pain. [44] Several studies reported that pathological change in 5-HT level have been associated with AD, anxiety and Depression.…”
Section: Discussionmentioning
confidence: 99%
“…However, the biological activity of 5-HT is not only regulated by its breakdown but also by its biosynthesis and intracellular handling (33). In 5-HT-synthesizing cells, the transmitter is packed into vesicles with the help of the vesicular monoamine transporter (VMAT) and is secreted if needed.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that developmental apoptosis during early embryonic MAO-A deficiency may be conferred by 5-Htr6. (33) including the mitogen-activated kinase ERK (34 -36), and 5-Htr6 has been suggested to activate ERK1/2 via Fyn kinase (37). ERK1/2 activates a number of downstream targets including Bcl-2 (38) and may therefore constitute a link between 5-HT signaling and the observed developmental defects.…”
Section: Figure 2 Inhibition Of Embryonic 5-ht Biosynthesis Rescues mentioning
confidence: 99%